Universal Anticancer Cu(DTC)2 Discriminates between Thiols and Zinc(II) Thiolates Oxidatively. Issue 18 (26th March 2019) - Xu, Luyan; Xu, Jialin; Zhu, Jingwei; Yao, Zijian; Yu, Na; Deng, Wei; Wang, Yu; Lin, Bo‐Lin
Abstract: Aerobic organisms must rely on abundant intracellular thiols to reductively protect various vital functional units, especially ubiquitous zinc(II) thiolate sites of proteins, from deleterious oxidations resulting from oxidizing environments. Disclosed here is the first well‐defined model study for reactions between zinc(II) thiolate complexes and copper(II) complexes. Among all the studied ligands of copper(II), diethyldithiocarbamate (DTC) displays a unique redox‐tuning ability that enables copper(II) to resist the reduction by thiols while retaining its ability to oxidize zinc(II) thiolates to form disulfides. This work proves for the first time that it is possible to develop oxidants to discriminate between thiols and zinc(II) thiolates, alluding to a new chemical principle for how oxidants, especially universal anticancer Cu(DTC)2, might circumvent the intracellular reductive defense around certain zinc(II) thiolate sites of proteins to kill malignant cells. Abstract : Oxidation tunes : Diethyldithiocarbamate (DTC) displays a unique redox‐tuning ability that enables copper(II) to resist the reduction by thiols while retaining its ability to oxidize zinc(II) thiolates to form disulfides. These studies provide molecular‐level insights into treatments of cancers with copper(II)/disulfiram.